Endothelial SARS-CoV-2 infection is not the underlying cause of COVID-19-associated vascular pathology in mice - Gao, Siqi; Tang, Alan T.; Wang, Min; Buchholz, David W.; Imbiakha, Brian; Yang, Jisheng; Chen, Xiaowen; Hewins, Peter; Mericko-Ishizuka, Patricia; Leu, N. Adrian; Sterling, Stephanie; August, Avery; et al. (Frontiers in Cardiovascular Medicine, 2023)
Endothelial damage and vascular pathology have been recognized as major features of COVID-19 since the beginning of the pandemic. Two main theories regarding how severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) damages endothelial cells and causes vascular pathology have been proposed: direct viral infection of endothelial cells or indirect damage mediated by circulating inflammatory molecules and immune mechanisms. However, these proposed mechanisms remain largely untested in vivo. In the present study, we utilized a set of new mouse genetic tools developed in our lab to test both the necessity and sufficiency of endothelial human angiotensin-converting enzyme 2 (hACE2) in COVID-19 pathogenesis. Our results demonstrate that endothelial ACE2 and direct infection of vascular endothelial cells do not contribute significantly to the diverse vascular pathology associated with COVID-19.